A Group of Urartu Pins from the Ahlat, Erzurum, and Van Archeology Museums - Yiğitpaşa, Davut (Selcuk University, Inst Turkish Studies, 2023)
The data on ornaments and jewelry in the Kingdom of Urartu has been obtained from archaeological excavations rather than written documents. This study covers the data on the pins obtained from the Urartu centers in the Eastern Anatolia Region and mostly from their necropoleis. From this point of view, we analyzed the pins in Van, Ahlat, and Erzurum Archeology Museums in this study. Pins, one of the types of jewelry used for decoration, are generally thin, flat, cylindrical and mostly made of metal, and used for sewing clothes and attaching the ends of the clothes and the hair. The pin consists of a head, body and tip shaped in various ways. Some archaeological finds include a crown decorated with plant or animal figures on the head and elements called torus and bracelets on which it is placed. On the other hand, the body consists of a hole and a pin that tapers toward the tip. We analyzed the chronology, meanings, usage methods, and construction techniques of Urartian pins, which consist of animal heads, animal figures, fruit and plant heads, bud and knot heads, and flat heads. We obtained results by dating the settlement finds within the Urartu State's borders and the contemporary neighboring region by conducting analogies between them. We also tried to identify the symbolic meanings Urartian pins can have as protection from evil, magic, decoration, status indicators, and the belief that the person will be protected forever after death.
Keywords: Van Museum; Urartian; Bronze; Jewelry; Pin